Analisis Pengaruh Kondisi Infrastruktur terhadap Kinerja Pelayanan Angkutan Penyeberangan di Pelabuhan Bolonan - Raintung, Arnetha; Beati, Tri Kurniadi; Pangalila, Deyce; Ndabuke, Yapson; Peginusa, Stefani Switly (Jurnal Teknik Sipil Terapan (JTST), 2026)
This study examines the service performance and infrastructure conditions at the Bolonan Ferry Port, as part of the maritime transportation system that plays a crucial role in supporting connectivity within the archipelago. The main problem is the indication of a discrepancy between the condition of the port infrastructure and minimum service standards, which impacts the quality of service to service users. This study aims to analyze service performance and evaluate infrastructure conditions as a basis for improving transportation services. The method used is a descriptive quantitative approach with primary data collection through observation, questionnaires, interviews, and documentation, as well as secondary data from relevant agencies. Data analysis uses a Service Quality approach that covers five dimensions: safety, security, comfort, ease/affordability, and equality. All research instruments have been tested for validity and reliability and are deemed suitable for further analysis. The results show that service performance is in the fairly good category, with the highest scores for the equality and safety aspects, while the comfort and security aspects received the lowest scores. This condition is in line with the finding that port infrastructure is still inadequate, especially in waiting room facilities, toilets, lighting, passenger lanes, and security facilities. Thus, it can be concluded that there is a close relationship between infrastructure conditions and service performance, so that infrastructure improvement is an important factor in improving the overall quality of port services. Keywords: Sea transportation; Ferry ports; Port infrastructure; Service performance; Service quality.